PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN SISWA SISWI SMA PANJURA MALANG - Mochammad Mochammad; N. Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
AbstractThe objective of the research was to find out and to analyze to what extent the influence of service marketing mix and service quality on students’ satisfaction in senior high school panjura malang. This research uses descriptive quantitative with sampling technique with non probability sampling technique. The type of data used in the study is the time series with data collection procedures through the delivery of questionnaires to selected consumers as a sample. The result of the research showed that service marketing mix which consisted of product, location, process, people, physical evidence, and service quality which consisted of direct evidence, reliability, response, security, and empathy simultaneously had positive influence on students’ satisfaction. Keywords: service marketing mix, service quality, students’ satisfaction